Bacillus subtilis SsbA and dATP regulate RecA nucleation onto single-stranded DNA - Carrasco, Begoña; Manfredi, Candela; Ayora, Silvia; Alonso, Juan C. (DNA repair, 2008)
Bacillus subtilis RecA preferentially hydrolyzes dATP over ATP and supports an efficient DNA strand exchange reaction in the presence of dATP when compared to ATP. Saturating amounts of SsbA, independently of the order of addition, reduce the single-stranded (ss) DNA-dependent dATPase activity of RecA, and block the ATPase activity. SsbA added prior to RecA slightly stimulates the dATP-dependent DNA strand exchange activity, whereas added after RecA greatly enhances the extent of strand exchange. In the presence of ATP, 10 times more RecA is required to achieve a comparable level of strand exchange than in the presence of dATP. We propose that dATP binding and hydrolysis as well as SsbA provide different levels of regulation of the dynamic RecA nucleoprotein filament.